Determination of consistent patterns of suspiciousness in news texts - Atanayeva М.К.; Buldybayev Т.К.; Ospanova У.А.; Akoyeva И.Г.; Nurumov К.С.; Baimakhanbetov М.А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
This article presents the results of the analysis of the corpus of texts of Kazakhstani media in order to identify the patterns of suspicious informative features of unreliable news. The data obtained are based on expert analysis of 5,2 thousand news texts. The process of forming and marking the text corpus according to the selected informative features of reliability, tonality, bias, politicization and the presence of manipulative techniques is presented in stages. The paper also considers the issues of public response of news and their causes identifying factors affecting the popularity of news texts using statistical modeling. To improve the reliability of the results obtained in the course of testing on recognition of informative features in the news triangulation method was considered and applied. According to the results of this work, a number of consistent patterns were established for the machine learning procedure to determine the influence of a set of informative features on the popularity of news.